Kinematic characterisation of the lunge and the fleche in epee fencing: Two case studies - Bober, T.; Rutkowska-Kucharska, A.; Jaroszczuk, S.; Barabasz, M.; Woznica, W. (Polish Journal of Sport and Tourism, 2016)
Introduction. The aim of this study was to characterise the whole body dynamics and upper and lower joint kinematics during two common fencing steps: the lunge and the fleche. Material and methods. Two male competitive epee fencers were studied. Kinematics data were collected at 120 Hz (BTS Smart system) and ground reaction forces were measured at 120 Hz (Kistler platform). The resultant centre of gravity and end segment velocities were calculated. Temporal events were referenced to the horizontal ground reaction force. Time domain linear joint velocities were extracted. Results. At the whole-body level, the resultant centre of gravity velocity was higher during the fleche (2.64 and 2.89 m/s) than during the lunge (1.94 and 2.21 m/s). At the joint level, the wrist and elbow attained their peak velocities earlier than the proximal joint for both the lunge and the fleche for both athletes. Conclusions. The sequence of peak segmental velocities followed a distal to proximal sequence for both fencing steps.